2020
DOI: 10.1002/fsn3.1314
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and α‐glucosidase inhibitory capacity of nonextractable polyphenols in Mopan persimmon

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This may be due to the influence of non-phenolic compounds in the samples, as it was also mentioned in another report that foods that are rich in phenolic compounds did not always show a strong inhibitory effect on α-glucosidase [ 47 ]. Another report mentioned that compared with large molecular-weight phenolic compounds, smaller molecular-weight phenolic compounds such as catechins are more likely to bind to the active site of the enzyme and thus have a stronger inhibitory effect on α-glucosidase [ 48 ]. The molecular weight of hydrolysable tannins in Kakadu plums is mainly between 600 and 1100 g/mol, which belongs to high molecular weight tannins [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the influence of non-phenolic compounds in the samples, as it was also mentioned in another report that foods that are rich in phenolic compounds did not always show a strong inhibitory effect on α-glucosidase [ 47 ]. Another report mentioned that compared with large molecular-weight phenolic compounds, smaller molecular-weight phenolic compounds such as catechins are more likely to bind to the active site of the enzyme and thus have a stronger inhibitory effect on α-glucosidase [ 48 ]. The molecular weight of hydrolysable tannins in Kakadu plums is mainly between 600 and 1100 g/mol, which belongs to high molecular weight tannins [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of EGCG in DMEM was assessed in assays that encompass distinct mechanisms of action: free-radical scavenging activity in relation to 2,2-diphenyl-1-picrylhydrazyl radical (DPPH), 2,2′ -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS⋅+) and ferric reducing antioxidant activity (FRAP). DPPH results were expressed as scavenging rate, ABTS and FRAP values were expressed as μmol of Trolox equivalent per g of each sample (Zhou et al, 2020).…”
Section: Antioxidant Activity Of Egcg In Dmemmentioning
confidence: 99%
“…In a study conducted by Zhou et al [ 8 ], the total content of EP and NEP present in Mopan persimmon was evaluated. The action against α-glucosidase of EP and NEP and their antioxidant capacity were also compared.…”
Section: In Vitro Digestion Studies Of Persimmon and Derived Productsmentioning
confidence: 99%
“…Thus, NEP was the most effective antioxidant in persimmon fruit after digestion. Nevertheless, Zhou et al [ 8 ] suggested further investigations to explain the composition and structure of EP and NEP to clarify their differences in biological activities.…”
Section: In Vitro Digestion Studies Of Persimmon and Derived Productsmentioning
confidence: 99%
See 1 more Smart Citation